Effect of Microstructure on the Thermal Properties of Sintered Iron-copper Composites - Caroline Velasques Ugarteche; Kaline Pagnan Furlan; Rafaela do Vale Pereira; Gabriel Trindade; Roberto Binder; Cristiano Binder; Aloisio Nelmo Klein (Materials Research, 2015)
Copper is a well know material for use as heat sink or heat exchanger. However, copper has a considerable low tensile strength and temperature limit. A material that has a good thermal conductivity, low cost, but also resistance is the desired. Effects of copper on the sintering and thermal properties of iron-copper composites produced by powder metallurgy and Fe on copper-iron composites have been investigated. Copper and iron were varied from 20 to 80 vol.% in the samples, alternating the continuous phase. Sintering studies were performed by in-situ dilatometry aiming to define the proper conditions for sintering, without swelling normally associated with copper. Results indicate that the type of sintering, final microstructure, specially the phases relation and distribution and not only the amount of copper, have a great effect into the thermal properties. By controlling the sintering parameters, it is possible to obtain dimensionally stable samples with higher thermal conductivity and lower copper amount.